2020
DOI: 10.1002/aoc.5607
|View full text |Cite
|
Sign up to set email alerts
|

Palladium supported on metal–organic framework as a catalyst for the hydrogenation of nitroarenes under mild conditions

Abstract: Sustainable development demands an environmentally friendly and efficient method for the hydrogenation of organic molecules, including the hydrogenation of functionalized nitroarenes. In this study, a highly active and selective metal–organic framework‐supported palladium catalyst was prepared for the catalytic hydrogenation of nitroarenes. High selectivity (>99%) and excellent yield (98%) of aniline were realized after 2 hours in ethanol under hydrogen (1 atm) at room temperature. The reductions were successf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 44 publications
0
12
0
Order By: Relevance
“…However, these attempts resulted in side reactions such as desulfurization, dearomatization, and C–S bond cleavage. Nevertheless, some studies have reported the use of sulfur-tolerant catalysts for the hydrogenation of sulfur-containing nitroarenes. Pd nanoparticles (NPs) doped or alloyed with other elements, such as Zn, S, and P, have been reported as active catalysts; however, they require harsh reaction conditions (H 2 > 30 bar). ,, Other reports only focused on a simple sulfur-containing nitroarene, p -nitrothioanisole, and the applicability of the catalysts for more complex sulfur-containing nitroarenes was not investigated. Consequently, the development of highly active and robust catalysts for the hydrogenation of sulfur-containing nitroarenes remains a challenge.…”
Section: Introductionmentioning
confidence: 99%
“…However, these attempts resulted in side reactions such as desulfurization, dearomatization, and C–S bond cleavage. Nevertheless, some studies have reported the use of sulfur-tolerant catalysts for the hydrogenation of sulfur-containing nitroarenes. Pd nanoparticles (NPs) doped or alloyed with other elements, such as Zn, S, and P, have been reported as active catalysts; however, they require harsh reaction conditions (H 2 > 30 bar). ,, Other reports only focused on a simple sulfur-containing nitroarene, p -nitrothioanisole, and the applicability of the catalysts for more complex sulfur-containing nitroarenes was not investigated. Consequently, the development of highly active and robust catalysts for the hydrogenation of sulfur-containing nitroarenes remains a challenge.…”
Section: Introductionmentioning
confidence: 99%
“…Compared to classic methods such as Bechamp reduction [13] which are time consuming, and reactions conducted in harsh acidic conditions producing large amounts of waste, catalytic hydrogenation using transition metals catalyst is highly clean, efficient and compatible with industrial applications. Among different metals used for reduction of nitro groups, Pd catalysts catalyze this reaction very efficiently with the formation of fewer byproducts [14][15][16][17][18][19][20][21][22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…First, the slow gas−liquid−solid mass transfer rate in batch reactors results in a long reaction time and relatively low efficiency. 25 For instance, Bao et al 26 utilized palladium supported on a metal− organic framework as a catalyst for the hydrogenation of 5nitroisoquinoline. The yield of 5-aminoisoquinoline (90%) was obtained with a reaction time of 3 h and more than 5% 5nitroisoquinoline was detected in the product, indicating low reaction efficiency.…”
Section: ■ Introductionmentioning
confidence: 99%